2011
DOI: 10.1212/wnl.0b013e3182299e13
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors and clinical phenotype in familial and sporadic primary blepharospasm

Abstract: The new information from this large family-based study on primary blepharospasm strongly supports eye diseases and coffee as risk factors for blepharospasm. The finding that the 2 environmental exposures exerted a similar influence on familial and sporadic blepharospasm, together with the convergent phenotypic expression in familial and sporadic cases, implies that familial and sporadic blepharospasm probably share a common etiologic background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
(16 reference statements)
1
35
0
Order By: Relevance
“…Patients with blepharospasm report photosensitivity and some find relief with tinted spectacles 28. Environmental studies in blepharospasm have shown that eye symptoms are reported more frequently prior to onset11 and tend to be more prevalent in the year prior to onset of spasms 8. Diseases of the anterior ocular segment (blepharitis, conjunctivitis) have been shown to be significantly related to blepharospasm, but not other ocular diseases such as glaucoma and cataracts 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with blepharospasm report photosensitivity and some find relief with tinted spectacles 28. Environmental studies in blepharospasm have shown that eye symptoms are reported more frequently prior to onset11 and tend to be more prevalent in the year prior to onset of spasms 8. Diseases of the anterior ocular segment (blepharitis, conjunctivitis) have been shown to be significantly related to blepharospasm, but not other ocular diseases such as glaucoma and cataracts 7.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors may influence disease penetrance and phenotype expression 7–9. Patients with cervical dystonia, compared with their unaffected siblings, have a history of more frequent car accidents with hospital attendance;10 anterior segment eye disease has been suggested to be a risk factor for blepharospasm,11 whereas coffee drinking appears protective 12. Cervical dystonia appears to be the most frequent phenotype in northern Europe, whereas blepharospasm seems more frequent in southern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The use of siblings as control participants strengthens the relevance of this study because approximately half will carry potentially causative genes. Although a case-sibling study design is at risk of over-matching because matched siblings share environmental exposures, such matching would obscure weak associations and highlight more influential associations 14. A case-sibling study is immune to population stratification bias15 and, for rare genes, it can lead to improved efficiency in the estimation of a gene-environment interaction 16…”
Section: Discussionmentioning
confidence: 99%
“…BPS is a primary adult-onset dystonia of unknown etiology, but multiple environmental and genetic factors are likely implicated 10 . This study was undertaken to explore different clinical correlation of the disease, which could provide clues as to the etiopathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, few subjects reported previous ocular disease, such as glaucoma. A recently published well designed study found an evidence of ocular disease such as dry eye, blepharitis and keratoconjuctivitis in 50 of 140 patients with BPS 10 . Previous studies have showed non-significant associations between alcohol use, hypertension and minor head trauma (without loss of consciousness) with BPS 13 .…”
Section: Demographic and Clinical Featuresmentioning
confidence: 99%